Deep Sequencing of Small RNAs in the Whitefly Bemisia tabaci Reveals Novel MicroRNAs Potentially Associated with Begomovirus Acquisition and Transmission - Daniel K. Hasegawa; Md Shamimuzzaman; Wenbo Chen; Alvin M. Simmons; Zhangjun Fei; Kai-Shu Ling (Insects, 2020)
The whitefly Bemisia tabaci (Gennadius) is a notorious insect vector that transmits hundreds of plant viruses, affecting food and fiber crops worldwide, and results in the equivalent of billions of U.S. dollars in crop loss annually. To gain a better understanding of the mechanism in virus transmission, we conducted deep sequencing of small RNAs on the whitefly B. tabaci MEAM1 (Middle East-Asia Minor 1) that fed on tomato plants infected with tomato yellow leaf curl virus (TYLCV). Overall, 160 miRNAs were identified, 66 of which were conserved and 94 were B. tabaci-specific. Among the B. tabaci-specific miRNAs, 67 were newly described in the present study. Two miRNAs, with predicted targets encoding a nuclear receptor (Bta05482) and a very-long-chain (3R)-3-hydroxyacyl-CoA dehydratase 2 (Bta10702), respectively, were differentially expressed in whiteflies that fed on TYLCV-infected versus uninfected plants. To better understand the regulatory effects of identified miRNAs and their target genes, we correlated expression profiles of miRNAs and their target transcripts and found that, interestingly, miRNA expression was inversely correlated with the expression of ~50% of the predicted target genes. These analyses could serve as a model to study gene regulation in other systems involving arthropod transmission of viruses to plants and animals.